O sistema de produção de carne suína avipal e as estratégias da empresa voltadas para a exportação - Antunes, Mônica da Pieve (2005)
This work analyzed the system of production of swine meat of the Avipal company, as well as identified the main no tariff trade barriers and evaluated the strategies of the Avipal directed toward the main external market, the Russian. The boardings on production systems, strategy administration, international trade and trade barriers had guided the analysis. The methodology used for the development of the work was the descriptive, approaching the study of case of the Avipal Company. One concluded that the Company adopts the integrated system of production, between producers of swines and agroindústria, what greater confers it has controlled on the product and gives competitive advantage in the international market. The strategies used for the Company are tied with the integrated production, the diversification of markets and the technological innovation. In a ampler direction, it was evidenced that the strategies strong are tied to the requirements of its main purchaser, the Russia, which establishes quotas of importation and imposes a rigorous fitossanitário control. The diversification of markets was used by the Company due the uncertainties that involve the establishment of quotas and the fitossanitário control. The technological innovation occurred through the changes in the organization of the production and the process.